2018
DOI: 10.1002/jmrs.280
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice radiation therapists: an Australian context

Abstract: The purpose of this scoping review is to examine the literature regarding the development, implementation, scope and extent of Advanced Practice Radiation Therapist (APRT) roles in Australia in peer reviewed journals, government reports, conference proceedings and reports. A search was undertaken of PubMed, Web of Science and CINAHL, the ASMIRT website and, and Google Scholar to identify relevant documents. Combinations of keywords with Boolean operators ((advanced practice) OR (advanced practitioner) OR (spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Although references do support examples of AP, individuals working in new AP roles should be encouraged to add research to the evidence base. By clearly quantifying benefit, these posts can gain further recognition [17].…”
Section: Estro Rttc Definitionmentioning
confidence: 99%
“…Although references do support examples of AP, individuals working in new AP roles should be encouraged to add research to the evidence base. By clearly quantifying benefit, these posts can gain further recognition [17].…”
Section: Estro Rttc Definitionmentioning
confidence: 99%
“…The development and integration of advanced practice in radiation therapy internationally was seen to address problems such as oncology staff shortages, expansion and improvement of cancer services, career development and staff retention and recruitment. Aligning with international models, the development of advanced practice in radiation therapy in Australia has been identified as an opportunity to extend clinical roles and to improve coordination of care, efficiency and productivity …”
Section: Introductionmentioning
confidence: 99%
“…RTs are highly trained professionals working in many areas of practice as clinical practitioners, educators/trainers, managers, and researchers. Many occupy roles as Advanced Practitioner RTs in countries such as Australia, the United Kingdom, Canada, New Zealand, and Ireland 14,15 and have taken on tasks once traditionally completed by radiation oncologists or medical physicists. 16 In job advertisements, titles such as Clinical Leads, Specialist or Consultant Practitioners and Charge RTs are now common.…”
Section: Changes In the Radiation Therapy Workforce Profilementioning
confidence: 99%
“…The authors also reported leadership skills were demonstrated in the areas of project management, technical innovation, and practice implementation. 16 In the Australian context, Hilder et al 14 also discussed the Advanced Practitioner roles and suggested the need to understand how these roles can improve service delivery and patient care.…”
Section: Changes In the Radiation Therapy Workforce Profilementioning
confidence: 99%